0377 A Strengths-Based Approach to Examine Obstructive Sleep Apnea in Black and White Patients. (27th May 2020) - Williams, N J; Butler, M; Roseus, J; Blanc, J; Barnes, A; Bubu, O M; Ebben, M; Krieger, A; Jean-Louis, G
Abstract: Introduction: The majority of studies on race/ethnic disparities in OSA are derived from a deficit-based perspective (i.e. >BMI, non-adherence to PAP). It would prove useful to identify which aspects are protective to inform potential treatment approaches. We focused on two potential factors: resilience and social support, in patients newly diagnosed with OSA. Given the high prevalence of insomnia complaints in patients with OSA, insomnia was our outcome of interest. Methods: 91 patients newly diagnosed with OSA provided demographic and socioeconomic status, sleep measures (Epworth, DBAS), resilience (Connor Davidson Resiliency Scale), social support (MOS Social Support Scale) and completed the Insomnia Severity Index. The cross-sectional associations between ISI, race/ethnicity, resilience, social support and their interaction effects were examined using linear regression models with covariate adjustment for participant age, sex and BMI. We ascertained total ISI score and individual items. Results: The sample was 34.1% black (n=31), mean age of 57.6 years, SD=13.6, 64.8% male (n=59), and mean BMI of 32.4, SD=7.04. Mean sleep duration (as reported by sleep diary) was 6.64, SD=1.35. Black, white differences were not observed for sleepiness (M=8.60; 10.43, p=0.11) or DBAS (M=4.61; M=5.04, p=0.30). Blacks, reported clinically significant insomnia (M=15.00, SD=7.17) compared to whites (M=12.02, SD=6.83, p=0.05). On the individual ISI items, blacks were significantly more likely to endorse difficulty falling asleep (M=1.58, SD=1.54; M=0.75, SD=0.93, p=0.002) and waking up too early (M=2.09, SD=1.26; M=1.45, SD=0.93, p=0.021) compared to whites. Resilience (M=30.04, SD=6.42) and social support scores (M=74.13, SD=21.36) did not differ by race/ethnicity. In adjusted linear analysis, resilience had significant effect on ISI score (b=-0.36, SE=0.12, p=0.003) but not social support (b=-0.06, SE=0.08, p=0.31). Conclusion: In this study we did not observe race/ethnic differences for sleepiness and dysfunctional beliefs about sleep. With respect to the protective factors, race/ethnic differences were not observed. Resilience, not social support, was related to insomnia complaints. Future studies should examine a variety of factors that may serve black and other racial/ethnic groups with OSA, and help elucidate protective processes. Support: K23HL125939